An Evaluation of Morphometric Characteristics of Honey Bee (Apis cerana) Populations in the Qinghai–Tibet Plateau in China - Xinru Zhang; Jian Lu; Xinying Qu; Xiao Chen (Life)
Apis cerana, a native type of honey bee in China, adapts well to the Qinghai–Tibet Plateau (QTP) environments with high altitude, cold, low oxygen, and strong radiation. In this study, we detected 40 morphological characteristics from 100 colonies in 49 regions. We not only evaluated the morphometric characteristics of honey bee populations in the QTP but also found that the pigmentation of labrum and tergite 2 in A. cerana is significantly different from that in Apis mellifera. Moreover, most morphological characteristics were correlated with environmental factors. Tibet and Qinghai could be distinctly separated. The cluster analysis indicated that Xunhua and Danba were far apart and formed a single cluster. Honey bees from Danba and Linzhichayu were correctly judged into corresponding populations. There was large morphometric diversity within the selected sampling areas of the Sichuan, Yunnan, and Gansu populations. Overall, our findings offer insights into the conservation and sustainable utilization of A. cerana in the QTP.